2020
DOI: 10.1097/ijg.0000000000001737
|View full text |Cite
|
Sign up to set email alerts
|

Visual Field Characteristics of Type I Boston Keratoprosthesis Patients Without Glaucoma

Abstract: Purpose: To determine visual field findings in Boston type 1-KPro (BI-KPro) patients without glaucoma. Characterize normal threshold values and global indices using standard automated perimetry and characterize visual field amplitude using Goldmann's manual perimetry.Methods: This cross-sectional prospective noninterventional study included patients (n = 6 patients, 6 eyes) with BI-KPro who had normal optical coherence tomography and fundoscopic evaluation of the optic disc and retina. None had a previous hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Visual field testing should also be attempted in all keratoplasty patients preoperatively and postoperatively, although poor visual acuity often impairs surveillance by this method [32]. Goldmann visual field (GVF) testing is commonly used to monitor visual fields in KPro eyes, with digital planimetric quantification of GVFs being investigated as a novel method for quantitative surveillance [33].…”
Section: Other Surveillance Methods In Penetrating Keratoplasty and K...mentioning
confidence: 99%
“…Visual field testing should also be attempted in all keratoplasty patients preoperatively and postoperatively, although poor visual acuity often impairs surveillance by this method [32]. Goldmann visual field (GVF) testing is commonly used to monitor visual fields in KPro eyes, with digital planimetric quantification of GVFs being investigated as a novel method for quantitative surveillance [33].…”
Section: Other Surveillance Methods In Penetrating Keratoplasty and K...mentioning
confidence: 99%
“… 27 A cross-sectional study that included 6 eyes that received the KPro device with no previous history of glaucoma, concluded that Goldmann manual perimetry was a reproducible test will all eyes showing good reliability indices. 30 Akpek et al tested the reliability of different glaucoma investigations in patients after Boston type 1 KPro implantation versus eyes with penetrating keratoplasty as controls. 31 They concluded that the Humphrey 10–2 visual field test and RNFL thickness with the OCT are both repeatable and reliable for detecting glaucomatous progression in KPro eyes.…”
Section: Introductionmentioning
confidence: 99%